PERLINDUNGAN HUKUM TERHADAP TENAGA KERJA PEREMPUAN MENURUT SISTIM HUKUM DI INDONESIA - Balthasar Watunglawar; Karel Wowor; Jocefina Tendean (SOSCIED, 2023)
The purpose of this study is to analyze and describe the forms of legal protection for workers that can be given to women workers according to Law Number 13 of 2003 concerning Manpower and knowing the factors influencing the implementation of legal protection for women workers. The research used normative juridical research with statutory approaches and conceptual approaches. Data obtained through documentation and interviews were analyzed, described, explained, compared, and interpreted for conclution. The results of the study revealed that legal protection for women workers was related to clarity of status, equal treatment, and exercise of rights. In addition, factors that need to be considered were the relativity of law, the absence of an agreement between women workers and employers to strengthen gender in the workplace, the low awareness of employers about women's labor rights, the low bargaining position of women, the type and type of work, wrong perceptions of employers regarding labor force, and the company's play on the status and rights of women workers. To fulfill the desire for legal protection for women workers, the legal product must prohibit gender identification in the entire management process, the legal product must not be related to relativity in perception and implementation, the legal product must be rational and not have an ambiguous impact, and all regulatory formulations and company policies must in the light of Pancasila philosophy..